2008
DOI: 10.1124/jpet.108.142232
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Asialoglycoprotein Receptor on Nonparenchymal Cells forO-Linked Glycoproteins

Abstract: B cell-activating factor receptor 3 (BR3)-Fc is an IgG1-receptor dimeric fusion protein that has multiple O-linked glycosylation sites and sialylation levels that can vary in the manufacturing process. Increased sialic acid levels resulted from increased site occupancy with the O-linked N-acetylgalactosamine (GalNAc-Gal), but because the ratio of sialic acid per mole of oligosaccharide remained approximately 1, this led to increased asialo terminal GalNAc. Previous studies have demonstrated an effect of termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…The list of published studies on biodistribution of therapeutic proteins is gradually increasing but is still relatively sparse, with majority of studies focusing on tumor‐targeting agents. Several studies on biodistribution of therapeutic proteins beyond oncology have been published in the recent years to address a variety of issues, such as FcRn‐mediated effects,10 carbohydrate‐related effects,11, 12 and penetration across the blood–brain barrier 13…”
Section: Introductionmentioning
confidence: 99%
“…The list of published studies on biodistribution of therapeutic proteins is gradually increasing but is still relatively sparse, with majority of studies focusing on tumor‐targeting agents. Several studies on biodistribution of therapeutic proteins beyond oncology have been published in the recent years to address a variety of issues, such as FcRn‐mediated effects,10 carbohydrate‐related effects,11, 12 and penetration across the blood–brain barrier 13…”
Section: Introductionmentioning
confidence: 99%
“…23,[26][27][28][29][30][31][32][33] Thus, sialylation masks the terminal galactose residues, thereby protecting glycoproteins from hepatocyte and non-parenchymal liver cell internalization and subsequent lysosomal degradation. 24,34 Also, lubricin derived from osteoarthritis synovial fluid contains more monosialylated glycans compared with disialylated glycans in rheumatoid arthritis (RA) synovial fluid. 13 Given our data in which the S6.79 epitopes on lubricin molecules in normal plasma and serum are more sialylated than those in normal synovial fluid, it is possible that the increased sialylation in RA synovial fluid could be due to an increased presence of blood-derived lubricin.…”
Section: Discussionmentioning
confidence: 99%
“…There are several other Fc‐fusion molecules that also rely on sialylation in reducing the in vivo clearance. BR3–Fc‐fusion has multiple O‐linked glycosylation sites, and it has been shown that changes of the sialic acid content through the manufacturing process have a direct relationship with the PK properties . BR3–Fc molecules with high sialic acid content exhibited much higher systemic exposure following i.v.…”
Section: Impact Of Glycosylation On the Pk Of Mab And Fc‐fusion Proteinsmentioning
confidence: 99%
“…Some therapeutic mAbs also bear additional glycosylation in the Fab domain such as cetuximab at Asn 88 of the VH region . In addition, some of the Fc‐fusion partner molecules such as etanercept and B cell‐activating factor receptor 3 (BR3)–Fc also possess O‐linked glycans . Alteration of glycan compositions and structures can cause conformational changes of the Fc domain, which could change binding affinity to Fcγ receptors, resulting in changes of immune effector functions .…”
Section: Introductionmentioning
confidence: 99%